The effect of Prospective Science Teachers’ Achievement Levels in Procedures and Mathematical Logic Knowledge on their Declarative Knowledge about Newton’s Laws of Motion - İsmail Yılmaz; Necati Yalçın (Sakarya Üniversitesi Eğitim Fakültesi Dergisi)
The present paper is focused on the effect of prospective science teachers’ knowledge and achievement levels in mathematical logic on their declarative knowledge and achievement levels in Newton’s laws of motion. In addition, it focuses on the effect of their achievement level in procedures on their declarative knowledge and achievement levels in Newton’s laws of motion. In the study, the procedures required by the students for the subjects about declarative knowledge were measured through two independent measurement tools. These are the QMT2 and QMT3 that measured the procedures for formulas and the procedures for basic math respectively. It was concluded that the students’ knowledge level does not support their achievement level in a satisfactory way. Furthermore, it was discovered that their achievement level in the procedures support their achievement level in the subjects in a limited way. Their achievement level in the QMT2 was higher than their knowledge level in formulas, which is related to the semantic aspect of the problem/solution. Incorporating methods into education in a constant manner does not necessarily mean that a decent kind of education will be achieved. Diversification of educational processes is more likely to be useful than not to be useful. Educational processes should also include semiotics so that students are enabled to make contributions to the process by which they comprehend things. Semiotics is linked with the variable “formula”. Learning semiotic structures of formulas will result in an increase in students’ knowledge level in this variable.